2021
DOI: 10.1101/2021.08.24.457448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutation Y453F in the spike protein of SARS-CoV-2 enhances interaction with the mink ACE2 receptor for host adaption

Abstract: COVID-19 patients transmitted SARS-CoV-2 to minks in the Netherlands in April 2020.Subsequently, the mink-associated virus (miSARS-CoV-2) spilled back over into humans.Genetic sequences of the miSARS-CoV-2 identified a new genetic variant known as "Cluster 5" that contained mutations in the spike protein. However, the functional properties of these "Cluster 5" mutations have not been well established. In this study, we found that the Y453F mutation located in the RBD domain of miSARS-CoV-2 is an adaptive mutat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…While S373P and Q498R substitutions had no significant effect compared to D614G, the mink-adapted Y453F substitution led to enhanced usage of African green monkey, ferret, Chinese hamster, Syrian golden hamster, white-tailed deer, and swine ACE2 receptors. A previous report has indicated the Y453F substitution enhanced spike interaction with Mustela species ACE2 orthologs, including minks, ferrets and stouts, while not compromising human ACE2 usage (Figure 5I, Table 1) 40 . Our findings extend this report and provide further insights into the effect of Y453F substitution for other species' ACE2.…”
Section: Omicron Variants Display Distinct Ace2 Receptor Usage Compar...mentioning
confidence: 68%
See 1 more Smart Citation
“…While S373P and Q498R substitutions had no significant effect compared to D614G, the mink-adapted Y453F substitution led to enhanced usage of African green monkey, ferret, Chinese hamster, Syrian golden hamster, white-tailed deer, and swine ACE2 receptors. A previous report has indicated the Y453F substitution enhanced spike interaction with Mustela species ACE2 orthologs, including minks, ferrets and stouts, while not compromising human ACE2 usage (Figure 5I, Table 1) 40 . Our findings extend this report and provide further insights into the effect of Y453F substitution for other species' ACE2.…”
Section: Omicron Variants Display Distinct Ace2 Receptor Usage Compar...mentioning
confidence: 68%
“…Substitutions in the RBD have been linked to SARS-CoV-2 adaptation to new hosts, such as ferrets 39 , mouse 33 , mink 40 and white-tailed deer 41 . The ongoing dominance and circulation of Omicron VOCs pose a significant risk for reverse zoonosis and spill back into the humans.…”
Section: Omicron Variants Display Distinct Ace2 Receptor Usage Compar...mentioning
confidence: 99%
“…A cryo‐EM study of this variant's S protein found closed, one RBD ‘up’ and two RBD ‘up’ states [43]. Structural analysis indicated that the Y453F substitution in the RBD is a species‐specific adaptive mutation, increasing binding to mink ACE2 [43,104]. This mutated virus strain circulated among the farmed minks, eventually leading to the first known animal‐to‐human transmission of SARS‐CoV‐2 [105].…”
Section: Diversity Of Sars‐cov‐2 Mutationsmentioning
confidence: 99%
“…MUC1 encoding from Ala23 to Gly167 is expressed with a Fc tag at the C-terminus and purchased from Novoprotein (China). replacing viral nucleocapsid gene (N) were made as previously described 7 . Caco-2-N cells were infected with the trVLP to amplify viruses 28 .…”
Section: Muc1 Lf and α-La Suppress Several Existed Mutants Of Sars-cov-2 Infection And Replicationmentioning
confidence: 99%
“…In addition, the ongoing pandemic has resulted in several viral variants [3][4][5] . These variants may potentially alter viral transmission, pathogenicity, efficacy of drug treatment as well as the binding capacity of vaccine elicited antibodies [6][7][8][9] . In this situation, it raises the need of several effective drugs with low toxicity to treat this disease.…”
Section: Introductionmentioning
confidence: 99%